The Transformation of Housing Policy. The System of Incentives for Housing in the Construction of Quasi-Markets in Ecuador - Córdova, Marco Antonio (Íconos)
Drawing upon a neo-institutionalist economic framework, this article attempts to explain how the public policy instruments for housing policy have shaped the development of quasi- markets in the housing sector in Ecuador. We analyze the case of Ecuador and the implementation of the System of Incentives for Housing (Sistema de Incentivos para la Vivienda- SIV) beginning in 1998. Methodologically the study analyzes the conditions underpinning the functioning of quasi-markets in housing (market structure, information, transaction of costs, motivation and adverse selection), as well as of the evalution criteria of the model (efficiency, sensibility, choice and equity). The results illustrate contradictions between the logic of competition in the quasi-market model of social housing and the restrictions of access which are the result of the socio-economic conditions of the country.